ANALYSIS OF PHYTOCOMPONENTS IN THE METHANOLIC EXTRACT OF Justicia gendarussa Burm.f. - Wahyuni, Dwi Kusuma; Hamidah (Acta Scientiae et Intellectus, 2024)
Justicia gendarussa Burm.f. belongs to the family Acanthaceae. In local population of West Papua, it is used as male contracetive. The objective of this study is to identify the present in the methanolic extract of Justicia gendarussa Burm.f. by GC-MS analysis. Twenty grams of the powdered plant materials are subjected to three methanol washes followed by filtration of the combined filtrate through the filter paper, and evaporate to give a final yield of 7% extract. The extract is subjected to GC-MS analysis. The GC-MS analysis of the sample is performed using an Agilent 6980N Network GC System with autosample. Data handling is done using GC-MS solution software. The identification of compounds is based on comparison of their mass spectra with those of WILEY version 8.0 Libraries. Twenty three compounds are identified. The major constituents are 2-ethylidene-1-methyl-3-phenylimidazolidine, 9,12-Octadecadienoic acid (Z,Z), and 5,6,8,9-tetramethoxy-2-methylpepero (3,4,5-jk)-9,10-dihydrophenanthracene.